An improved grey wolf optimizer for wrapper feature selection using harris hawks optimization - ALI AL-WAJIH, RANYA AHMED ABDO (2021)
The obtained data is frequently accompanied by a high amount of noise, which is generated by flaws in the data gathering technology utilised or by the data source itself